APPLICATION OF TURBULENT APPROACH TO THE KNOWLEDGE OF THE ECONOMIC SYSTEMS - Shkarlet, Serhii; Dubyna, Maksym (Науковий вісник Полісся, 2017)
Urgency of the research. Importance of the turbulent approach use to the cognition of the regularities of the economic systems development becomes the component of their research considering existence of these systems during the recent time in extremely and chaotic conditions of functioning . Target setting. Taking into consideration high stochastic level of the economic processes which can be observed in the development of many economic systems and which are due to the external and internal factors, it is appropriate to deepen the theoretical component of the turbulent approach use of the scientific researches for the cognition of such systems. Actual scientific research and issues analysis. To the scientists that were involved in the research of the turbulence phenomena by cognition the economic objects should be related the following ones : Grosul V. A., Demianchuk I .A., Zhuravliova G. P., Zakharchenko P. V., Kaslione J. A., Masliuk Ye. V., Yaroshenko R. F. and others. Theoretical aspects of the turbulent approach use and grounding its essence are met in the scientific researches of Gerasymov E. B., Burlachkov V., Trubetskov D. I., Makarov N. N. Uninvestigated parts of general issue defining. However, notwithstanding numerous scientific works within which the regularities and peculiarities of the turbulence phenomena on the development of the systems of different nature are investigated, deepening require theoretical principles of the essence identification of the turbulent approach, definition the peculiarities of its use for studying the objects of different nature. The research objective. Thus, the actual become issues of the theoretical grounding of the turbulent approach use to the economic systems cognition. Statement of the main material. Within the article essence of the turbulent approach is grounded and peculiarities of its use to the cognition of the economic systems are defined. In particular, the conceptual approaches of the turbulence identification as a separate phenomena are detailed. As well, the scheme of the turbulence influence on the systems of different nature is described, factors of the turbulent processes are identified. It was suggested to consider the turbulent process as the algorithm of study of the systems of different nature essence of which lie in cognition of such systems that function in not predictable, chaotic and changeable conditions that threaten its stability and lead to arise of the high entropy level in their frames. Conclusions. Use of the turbulent approach to the economic systems cognition gives the possibility to deepen the system of the methods of the economic researches by new approach that is directed to the investigation such systems in chaotic world where further transformations of the environment are hardly predictable.